Clearing the Pathways to Self-Transcendence - Worth, Piers; Smith, Matthew D. (Frontiers in Psychology, 2021)
‘Self-transcendence’ is proposed as a way in which individuals might find relief and support in the context of COVID-19, as well as other times of uncertainty. However, the authors propose that the multiple definitions of self-transcendence within existing literature lean towards the complex, sometimes obscure, and imprecisely spiritual. A concern is that this creates a circumstance where the possibility of supporting self-transcendence in a wider population will become excluding in this complexity. In this paper, we have undertaken a critical summary review focused primarily on historical foundations of the concept of self-transcendence, and of key theoretical approaches in which self-transcendence and self-transcendent experiences are discussed, with the motive of finding a clarity to understanding self-transcendence and the pathways towards it.  We argue that this much needed clarity in our understanding of self-transcendence may serve as an inclusive and democratised resource in which to support wellbeing and resilience in the context of COVID and beyond.